1996
DOI: 10.1128/aem.62.7.2644-2646.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atrazine on Ochrobactrum anthropi membrane fatty acids

Abstract: Ochrobactrum anthropi is a gram-negative bacillus recognized as a human opportunist pathogen isolated in clinical specimens and not of clinical significance. We report a new aspect of this bacterium, that it has been isolated from activated sludge. In fact, it is able to grow on atrazine (2-chloro-4-ethylamino-6-isopropyl-amines-triazine) by utilizing it as the only source of carbon. Our results show that atrazine (0.03 g/liter) causes a dramatical increase in the degree of saturation of membrane fatty acids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 12 publications
(14 reference statements)
4
27
0
Order By: Relevance
“…Exposure to DEHP did not have this effect at either concentration. The increase in saturation was similar to that reported for Pseudomonas putida P8, and Ochrobactrum anthropi, after exposure to known membrane-disrupting compounds and is indicative of an increase in the ordering of membrane lipids to reduce fluidity [26,37]. The impact of DEP and DEHP on membrane composition was in agreement with predictions based on the lipophilic characteristics of both phthalates.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Exposure to DEHP did not have this effect at either concentration. The increase in saturation was similar to that reported for Pseudomonas putida P8, and Ochrobactrum anthropi, after exposure to known membrane-disrupting compounds and is indicative of an increase in the ordering of membrane lipids to reduce fluidity [26,37]. The impact of DEP and DEHP on membrane composition was in agreement with predictions based on the lipophilic characteristics of both phthalates.…”
Section: Resultssupporting
confidence: 84%
“…Such changes are indicative of membrane disruption, and have been reported as markers of environmental stress [23,24]. However, although reported for phenolic compounds such as phenol [25] and the s-triazine herbicide atrazine [26], membrane disruption has not been associated directly with phthalates [17]. Published K ow coefficients are 2.38 for diethyl phthalate (DEP) and 7.50 for di (2-ethyl hexyl) phthalate (DEHP) [5], indicating that of the two, only DEP will be membrane disruptive.…”
Section: Introductionmentioning
confidence: 99%
“…The microorganism was isolated from activated sludge contaminated with atrazine. Culture morphology and biochemical reaction in the API ID 32 E and ID 32 GN (Biome èrieux) system were consistent with the identi¢cation of O. anthropi [10].…”
Section: Microorganism Isolation and Identi¢cationsupporting
confidence: 66%
“…For this reason it is important to understand the structural, kinetic and immunological properties of the glutathione transferases of a wide number of bacterial strains. Here we report the puri¢cation and N-terminal sequence of a novel glutathione transferase from O. anthropi, a bacterium able to degrade atrazine [10]. We have studied the immunological properties of the enzyme of O. anthropi and compared the N-terminal sequence with known glutathione transferases puri¢ed from other bacterial strains.…”
Section: Introductionmentioning
confidence: 99%
“…These include herbicides, hemicellulose, anthracene, nicotine, phenol and other complex organic molecules including polycyclic aromatic hydrocarbons and crude oil. Ochrobactrum strains accumulate heavy metal ions and express degrading properties towards multiple antibiotics (Asano et al, 1992;van den Tweel et al, 1993;Laura et al, 1996;Sonke et al, 2005;Qiu et al, 2006). In our previous study, we found that Ochrobactrum sp.…”
Section: Introductionmentioning
confidence: 98%